Pengaruh Jenis Aktivator terhadap Karakteristik Karbon Aktif Berbahan Ampas Tebu - Zazira, Annisa Zia; Fachraniah, Fachraniah; Ridwan, Ridwan (Jurnal Teknologi, 2024)
A study was done to determine the effect of activator type on the properties of activated carbon generated from sugarcane bagasse. The goal of this research is to examine the effect of activator type and activation period on the quality of activated carbon derived from sugarcane bagasse. This study's procedure began with the manufacture of activated carbon from sugarcane bagasse. The dried sugarcane bagasse was heated until it produced charcoal. In 150 cc of each activator solution, 10 g of charcoal were dissolved. It was then heated and left for the set activation time treatment. Three experiments on the properties of activated carbon were performed, namely moisture content, ash content, and iodine adsorption capacity (I2) for activation times of 6 hours, 9 hours, 12 hours, 15 hours, and 18 hours. According to the findings of this study, the kind of activator had little effect on the moisture and ash content of activated carbon, but it had a considerable effect on the iodine adsorption capacity of activated carbon. Furthermore, the activation duration influences the moisture level, ash content, and iodine adsorption capacity of activated carbon. The moisture material, ash content, and iodine adsorption ability (I2 ) of activated carbon (AC) from sugarcane bagasse satisfied the criteria of the Indonesian National Standard (SNI) in this study. Bilimbi (Averrhoa bilimbi L.) was the most effective activator in this investigation, with an engagement time of 6 hours.